Pendampingan Pengelolaan Obat di Usaha Kesehatan Sekolah (UKS) Sekolah Dasar Muhammadiyah 16 dan 52 Bukit Duri JAKARTA - Dina Pratiwi; Kori Yati; Hari Sulistiyono; Wening Tri Mawanti; Nuraini Nuraini; Nala Masayu Sofika Arum; Alya Rahma Kirani; Emir Rizky Taptajani; Rijal Triyana Juniansyah (PPNI UNIMMAN, 2025)
School Health Business (UKS) is a program that aims to promote a healthy lifestyle among students. Health services at UKS include providing medicine for students who experience minor illnesses. However, a shortage of pharmacists in schools can increase the risk of errors in medication management and threaten patient safety. Teachers play an important role in providing first aid and coordinating medical emergencies at school. Teachers also play a role in providing education about health to students, including correct medication management. This activity aims to increase the understanding and awareness of UKS managers about the importance of correct medication management, as well as encouraging behavioral changes in obtaining, using, storing and disposing of medication (DAGUSIBU) correctly. The activities were carried out using counseling, outreach and mentoring methods for Teachers and students at SD Muhammadiyah 16 and 52.The results of the activity showed that there was an increase in teachers' and students' understanding of drug management, especially drug storage.